Karakteristik Wilayah Sebagai Determinan Penyebaran Malaria di Kabupaten Jepara - Raharjo, Mursid; Sutikno, Sutikno; Mardihusodo, Sugeng Juwono (Jurnal Kesehatan Lingkungan Indonesia, 2003)
ABSTRACT Background : Malaria in Jepara district is inequitable distribution. This is very important object specially to evaluate the correlation between the  geographical characteristics and the Anopheles aconitus  densities as a vector of malaria. The other object  is the correlation between the climatic changes and malaria incidence. Method : Based on the malaria incidence the area are segregated in 3 class, High Case Incidence (HCI), Medium Case Incidence(MCI),  and Low Case Incidence (LCI). The next stratification was  based on topography, with the interval  of  0-25 m, 26 –50 m, 51-75 m, 76 – 100 m, and more than 100 m above sea level. Research was done in the wet and dry season. Correlation between dependent and independent variable analyses  by  the Pearson Product Moment, and determinant coefficient analyses  to conclude the determinant  variable Result :  The results of the research showed determinant coefficient of  geographical characteristics to Anopheles aconitus densities 94,9% (R2 =0,949), with the correlation coefficient  0,974. Gradually the partial  impact of the geographical characteristic to the Anopheles aconitus densities  were : 1. humidity 64,96% 2.waste water treatment 36,6%; 3. solid waste management 32,15%; 4. salinity 23,33%; 5. population density 19,18%; 6.air temperature 16,48%; 7. topography 11,56%; 8.  vegetation densities 5,2%, if the other parameter do not calculated. Conclusion: Jepara district have deferent geographical characteristic that  fluctuatively as  the season, and regulated Anopheles aconitus distribution. The determinant parameter are humidity (64,96%), waste water treatment (36,6%) solid waste management (32,15%); salinity (23,33%,), population density (19,18%) air temperature (16,48%), topography (11,56%)  vegetation densities 5,2%, if the other parameter do not calculated. The geographical characteristic compose the special zone as a Anopheles aconitus habitat.   Key word : Geographical characteristic,  Anopheles aconitus densities, determinant parameter.